INTERLEUKIN-6 IS A POTENTIAL TARGET FOR A CORRECTION OF ENDOTHELIAL DYSFUNCTION ASSOCIATED WITH LOW-GRADE SYSTEMIC INFLAMMATION - Darya Kostina; Tatyana Pokrovskaya; Evgeniya Beskhmelnitsyna (Belgorod National Research University, 2017)
Introduction: One of pathogenetic links of development of endothelial dysfunction, as an early marker of cardiovascular disease and comorbidity, is a low-grade systemic inflammation. In this regard, correction of cytokines imbalance is one of the possible ways of prevention and treatment of major chronic noninfectious diseases. Aims: To study the endothelium protective effects of anti-IL-6 receptor monoclonal antibodies tocilizumab in experimental preclinical studies in a model of endothelial dysfunction associated with the low-grade systemic inflammation. Methods: The study was performed with 40 white male Wistar rats. The endothelial dysfunction associated with the low-grade systemic inflammation and oxidative stress was produced by sequential administration of gentamicin, bacterial lipopolysaccharide and N-nitro-L-arginine methyl ester. The administration of tocilizumab (Actemra®, F. Hoffmann-La Roche Ltd, Switzerland) was performed at 6 day from the experiment start in doses of 4 mg/kg and 8 mg/kg once. The endothelium protective activity was studied at 34th day from the s the experiment start through the analysis of changes of pharmacological vascular tests and calculation of the endothelial dysfunction coefficient. The cytokine profile was assessed by measuring of serum concentrations of tumor necrosis factor-α, interleukin-6 and interleukin-10 by enzyme linked immunosorbent assay. Results: In the model of endothelial dysfunction associated with the low-grade systemic inflammation and oxidative stress, tocilizumab at the doses of 4 mg/kg and 8 mg/kg had the dose-dependent endothelium protective action that is logged to reduce of the endothelial dysfunction coefficient from 7.2±0.6 to 2.8±0.3 and 2.3±0.2, respectively. In addition, there was normalization of the cytokine profile in the form of lower serum concentrations of the tumor necrosis factor-α, interleukin-6 and interleukin-10. Conclusion: Tocilizumab (at the doses of 4 mg/kg and 8 mg/kg) after one dose delivery has a pronounced endothelium protective activity in the model of endothelial dysfunction associated with the low-grade systemic inflammation and oxidative stress and prevents of the cytokine profile imbalance.